Pelatihan Penggunaan Aplikasi SILPPM Pada Lembaga Penelitian dan Pengabdian Kepada Masyarakat di Universitas Mohammad Husni Thamrin - Agustino, Rano; Sopian, Abu; Djaali, Nur Asniati; Wiyatno, Agus; Saputro, Mohammad Ikhsan (Universitas Mohammad Husni Thamrin, 2021)
In the midst of the lively development of information technology applications nowadays, it has a good impact from various aspects. There are several aspects that have been affected by the development of information technology applications, one of which is administration in an organization or institution. Therefore, on this occasion we will take advantage of information technology applications to support administration in data collection at the Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) at Universitas Mohammad Husni Thamrin (UMHT) so that it can be done using applications or programs. The application or Sistem Informasi Lembaga Penelitian dan Pengabdian kepada Masyarakat (SILPPM) is expected to improve LPPM's performance in terms of data collection for lecturers. In recording or collecting data in terms of activities related to LPPM such as research activities, publication of lecturers' articles, scientific works and others. To apply the SILPPM application to LPPM UMHT, socialization is needed to the user so that this application can be used properly. Therefore, it is necessary to hold this community service activity with the aim of disseminating the SILPPM application to admins or users of LPPM employees by providing training in accordance with the modules (manual books) that have been prepared in advance.